Viscoelasticity within the framework of isothermal two-mechanism models - Kröger, N.H.; Böhm, M.; Wolff, M. (Computational materials science, 2012)
► We present an extension of the classical description for linear viscoelasticity within the framework of two-mechanism models. ► The presented viscoelastic-material model based on the model of two Kelvin–Voigt bodies in series. ► Contrary to the classical rheological model, we allow an interaction between the two Kelvin–Voigt bodies. ► Including the interaction, our model is capable of predicting material behaviour such as ratcheting. ► Numerical simulations are provided for a one-dimensional rod stimulated by an asymmetric cyclic stress. The subject of this article is an extension of the classical description for linear viscoelasticity within the framework of two-mechanism models (generally, multi-mechanism models). Multi-mechanism models are mainly used to describe plastic material behaviour. We present a viscoelastic-material model based on the model of two Kelvin–Voigt bodies in series. Contrary to the classical rheological model, we allow an interaction between the two Kelvin–Voigt bodies. Our model is able to reproduce the classic linear viscoelasticity and with including the interaction qualitatively capable of predicting material behaviour such as ratcheting. We underline this by providing qualitative numerical simulations for a one-dimensional rod stimulated by an asymmetric cyclic stress.